Effect of Foot Reflexology on Reduction of Labour Pain Among Primigravida Mothers - Mohan, RN, RM, Manju; Varghese, RN, RM, Linda (International Journal of Therapeutic Massage & Bodywork, 2020)
Background: Reflexology may help induce labour and reduce pain during childbirth. Fear of pain associated with childbirth leads to increase in the irregular use of cesarean method. Purpose: This study was performed to evaluate the effect of reflexology on relieving labour pain and assess the recipient’s opinion regarding foot reflexology. Setting: The study taken place in the labour room, Amrita Institute of Medical Sciences, Kerala, South India. Participants: 50 primigravida patients experiencing labour. Research Design: A quasi-experimental study design was used. Subjects were selected by convenience sampling technique with the first 25 patients allocated to the experimental group and the successive 25 primigravida mothers to a time-control group, to avoid data contamination. Intervention: Intervention consisted of foot reflexology applied by a trained therapist to five pressure points of both feet that correspond to the uterus. Total intervention time lasted 20 minutes. Control group rested quietly for 20 minutes to serve as a time control. Main Outcome Measure(s): Pain associated with labour was recorded on a visual analogue scale immediately prior to intervention, and at 20- and 40-minutes postintervention. Patient satisfaction with reflexology treatment was recorded. Results: Mean baseline pain score in foot reflexology group was significantly reduced across the study timeframe relative to control group (p < .001). Post hoc tests confirmed a reduction in labour pain at both the 20-min (p < .001, 95%CI 0.764–1.796) and 40-min (p < .001, 95%CI 0.643–1.677) time points. Eighty-one per cent of patients would recommend reflexology during labour. Conclusion: The findings showed that foot reflexology was effective in relief of labour pain, with a high degree of patient satisfaction in primigravida mothers.